On the present state of the law of settlement and removal of paupers in Scotland - Alison, William P. (Statistical and Social Inquiry Society of Ireland, 1852)
It is well known that the part of the Legal Provision of the Poor which regulates their settlement, i.e., the district of the country from which each family may claim relief, is at present widely different in the three great divisions of Her Majesty's dominions. In England, the statute law on the subject is so complex, that it has long ago been stated by Dr. Burn "to be the work of an age to ascertain the law regarding settlements"; but the practical result of this excessive complication, to a great proportion of the natives of the country?I believe particularly to agricultural labourers?has been nearly the same as if there had been no settlement but by birth. "It is nearly useless for a working man," says Mr. Eevans, long officially familiar with the English Poor-law, "to attempt to obtain work beyond the bounds of his parish." In Scotland, a settlement is acquired at present by five years' residence and independent industry in any one parish (although under conditions of which I shall say a few words presently); while in Ireland there is no law enforcing settlement in any one parish or union; although every union, in which a person falls destitute and applies for relief, is bound to give relief, at least by admission to the workhouse.
Read at the statistical section of the British association at Belfast, on Monday, 6th September, 1852
Keywords: Scottish poor law; Settlement law; 314.15